Seasonal to Decadal Predictions of Arctic Sea Ice: Challenges and Strategies - National Research Council (The National Academies Press, 2012)
Recent well documented reductions in the thickness and extent of Arctic sea ice cover, which can be linked to the warming climate, are affecting the global climate system and are also affecting the global economic system as marine access to the Arctic region and natural resource development increase. Satellite data show that during each of the past six summers, sea ice cover has shrunk to its smallest in three decades. The composition of the ice is also changing, now containing a higher fraction of thin first-year ice instead of thicker multi-year ice. Understanding and projecting future sea ice conditions is important to a growing number of stakeholders, including local populations, natural resource industries, fishing communities, commercial shippers, marine tourism operators, national security organizations, regulatory agencies, and the scientific research community. However, gaps in understanding the interactions between Arctic sea ice, oceans, and the atmosphere, along with an increasing rate of change in the nature and quantity of sea ice, is hampering accurate predictions. Although modeling has steadily improved, projections by every major modeling group failed to predict the record breaking drop in summer sea ice extent in September 2012. Establishing sustained communication between the user, modeling, and observation communities could help reveal gaps in understanding, help balance the needs and expectations of different stakeholders, and ensure that resources are allocated to address the most pressing sea ice data needs. Seasonal-to-Decadal Predictions of Arctic Sea Ice: Challenges and Strategies explores these topics.
Keywords: Earth Sciences

Linkages Between Arctic Warming and Mid-Latitude Weather Patterns: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
The Arctic has been undergoing significant changes in recent years. Average temperatures are rising twice as fast as they are elsewhere in the world. The extent and thickness of sea ice is rapidly declining. Such changes may have an impact on atmospheric conditions outside the region. Several hypotheses for how Arctic warming may be influencing mid-latitude weather patterns have been proposed recently. For example, Arctic warming could lead to a weakened jet stream resulting in more persistent weather patterns in the mid-latitudes. Or Arctic sea ice loss could lead to an increase of snow on high-latitude land, which in turn impacts the jet stream resulting in cold Eurasian and North American winters. These and other potential connections between a warming Arctic and mid-latitude weather are the subject of active research. Linkages Between Arctic Warming and Mid-Latitude Weather Patterns is the summary of a workshop convened in September 2013 by the National Research Council to review our current understanding and to discuss research needed to better understand proposed linkages. A diverse array of experts examined linkages between a warming Arctic and mid-latitude weather patterns. The workshop included presentations from leading researchers representing a range of views on this topic. The workshop was organized to allow participants to take a global perspective and consider the influence of the Arctic in the context of forcing from other components of the climate system, such as changes in the tropics, ocean circulation, and mid-latitude sea surface temperature. This report discusses our current understanding of the mechanisms that link declines in Arctic sea ice cover, loss of high-latitude snow cover, changes in Arctic-region energy fluxes, atmospheric circulation patterns, and the occurrence of extreme weather events; possible implications of more severe loss of summer Arctic sea ice upon weather patterns at lower latitudes; major gaps in our understanding, and observational and/or modeling efforts that are needed to fill those gaps; and current opportunities and limitations for using Arctic sea ice predictions to assess the risk of temperature/precipitation anomalies and extreme weather events over northern continents.
Keywords: Earth Sciences

Opportunities to Use Remote Sensing in Understanding Permafrost and Related Ecological Characteristics: Report of a Workshop - National Research Council (The National Academies Press, 2014)
Permafrost is a thermal condition -- its formation, persistence and disappearance are highly dependent on climate. General circulation models predict that, for a doubling of atmospheric concentrations of carbon dioxide, mean annual air temperatures may rise up to several degrees over much of the Arctic. In the discontinuous permafrost region, where ground temperatures are within 1-2 degrees of thawing, permafrost will likely ultimately disappear as a result of ground thermal changes associated with global climate warming. Where ground ice contents are high, permafrost degradation will have associated physical impacts. Permafrost thaw stands to have wide-ranging impacts, such as the draining and drying of the tundra, erosion of riverbanks and coastline, and destabilization of infrastructure (roads, airports, buildings, etc.), and including potential implications for ecosystems and the carbon cycle in the high latitudes. Opportunities to Use Remote Sensing in Understanding Permafrost and Related Ecological Characteristics is the summary of a workshop convened by the National Research Council to explore opportunities for using remote sensing to advance our understanding of permafrost status and trends and the impacts of permafrost change, especially on ecosystems and the carbon cycle in the high latitudes. The workshop brought together experts from the remote sensing community with permafrost and ecosystem scientists. The workshop discussions articulated gaps in current understanding and potential opportunities to harness remote sensing techniques to better understand permafrost, permafrost change, and implications for ecosystems in permafrost areas. This report addresses questions such as how remote sensing might be used in innovative ways, how it might enhance our ability to document long-term trends, and whether it is possible to integrate remote sensing products with the ground-based observations and assimilate them into advanced Arctic system models. Additionally, the report considers the expectations of the quality and spatial and temporal resolution possible through such approaches, and the prototype sensors that are available that could be used for detailed ground calibration of permafrost/high latitude carbon cycle studies.
Keywords: Earth Sciences

Toward an Integrated Arctic Observing Network - National Research Council (The National Academies Press, 2006)
Observable changes with regional and global implications, such as warming temperatures and reduced sea ice, are taking place across the Arctic. However, the record of Arctic observations suffers from incomplete geographic coverage and limited duration, and measurements are not well coordinated. This makes it difficult to comprehensively describe current conditions in the Arctic, let alone understand the changes that are underway or their connections to the rest of the Earth system. The U.S. National Science Foundation asked for guidance to help design a pan-arctic observing network. This book outlines the potential scope, composition, and implementation strategy for an arctic observing network. Such an integrated, complete, and multidisciplinary environmental observing network will improve society's understanding of and ability to respond to ongoing systemic changes in the Arctic and its capability to anticipate, predict, and respond to future change both in the Arctic and around the globe. The network would build on and enhance existing national and international efforts and deliver easily accessible, complete, reliable, timely, long-term, pan-arctic observations. Because many potential components of the network already exist or are being planned, and because of the surge of activity during the International Polar Year, there is an immediate opportunity for major progress.
Keywords: Earth Sciences

Responding to Oil Spills in the U.S. Arctic Marine Environment - Transportation Research Board; National Research Council (The National Academies Press, 2014)
U.S. Arctic waters north of the Bering Strait and west of the Canadian border encompass a vast area that is usually ice covered for much of the year, but is increasingly experiencing longer periods and larger areas of open water due to climate change. Sparsely inhabited with a wide variety of ecosystems found nowhere else, this region is vulnerable to damage from human activities. As oil and gas, shipping, and tourism activities increase, the possibilities of an oil spill also increase. How can we best prepare to respond to such an event in this challenging environment? Responding to Oil Spills in the U.S. Arctic Marine Environment reviews the current state of the science regarding oil spill response and environmental assessment in the Arctic region north of the Bering Strait, with emphasis on the potential impacts in U.S. waters. This report describes the unique ecosystems and environment of the Arctic and makes recommendations to provide an effective response effort in these challenging conditions. According to Responding to Oil Spills in the U.S. Arctic Marine Environment, a full range of proven oil spill response technologies is needed in order to minimize the impacts on people and sensitive ecosystems. This report identifies key oil spill research priorities, critical data and monitoring needs, mitigation strategies, and important operational and logistical issues. The Arctic acts as an integrating, regulating, and mediating component of the physical, atmospheric and cryospheric systems that govern life on Earth. Not only does the Arctic serve as regulator of many of the Earth's large-scale systems and processes, but it is also an area where choices made have substantial impact on life and choices everywhere on planet Earth. This report's recommendations will assist environmentalists, industry, state and local policymakers, and anyone interested in the future of this special region to preserve and protect it from damaging oil spills.
Keywords: Environment and Environmental Studies; Earth Sciences

The Arctic in the Anthropocene: Emerging Research Questions - National Research Council (The National Academies Press, 2014)
Once ice-bound, difficult to access, and largely ignored by the rest of the world, the Arctic is now front and center in the midst of many important questions facing the world today. Our daily weather, what we eat, and coastal flooding are all interconnected with the future of the Arctic. The year 2012 was an astounding year for Arctic change. The summer sea ice volume smashed previous records, losing approximately 75 percent of its value since 1980 and half of its areal coverage. Multiple records were also broken when 97 percent of Greenland's surface experienced melt conditions in 2012, the largest melt extent in the satellite era. Receding ice caps in Arctic Canada are now exposing land surfaces that have been continuously ice covered for more than 40,000 years. What happens in the Arctic has far-reaching implications around the world. Loss of snow and ice exacerbates climate change and is the largest contributor to expected global sea level rise during the next century. Ten percent of the world's fish catches comes from Arctic and sub-Arctic waters. The U.S. Geological Survey estimated that up to 13 percent of the world's remaining oil reserves are in the Arctic. The geologic history of the Arctic may hold vital clues about massive volcanic eruptions and the consequent release of massive amount of coal fly ash that is thought to have caused mass extinctions in the distant past. How will these changes affect the rest of Earth? What research should we invest in to best understand this previously hidden land, manage impacts of change on Arctic communities, and cooperate with researchers from other nations? The Arctic in the Anthropocene reviews research questions previously identified by Arctic researchers, and then highlights the new questions that have emerged in the wake of and expectation of further rapid Arctic change, as well as new capabilities to address them. This report is meant to guide future directions in U.S. Arctic research so that research is targeted on critical scientific and societal questions and conducted as effectively as possible. The Arctic in the Anthropocene identifies both a disciplinary and a cross-cutting research strategy for the next 10 to 20 years, and evaluates infrastructure needs and collaboration opportunities. The climate, biology, and society in the Arctic are changing in rapid, complex, and interactive ways. Understanding the Arctic system has never been more critical; thus, Arctic research has never been more important. This report will be a resource for institutions, funders, policy makers, and students. Written in an engaging style, The Arctic in the Anthropocene paints a picture of one of the last unknown places on this planet, and communicates the excitement and importance of the discoveries and challenges that lie ahead.
Keywords: Earth Sciences; Environment and Environmental Studies

National Security Implications of Climate Change for U.S. Naval Forces - National Research Council (The National Academies Press, 2011)
In response to the Chief of Naval Operations (CNO), the National Research Council appointed a committee operating under the auspices of the Naval Studies Board to study the national security implications of climate change for U.S. naval forces. In conducting this study, the committee found that even the most moderate current trends in climate, if continued, will present new national security challenges for the U.S. Navy, Marine Corps, and Coast Guard. While the timing, degree, and consequences of future climate change impacts remain uncertain, many changes are already underway in regions around the world, such as in the Arctic, and call for action by U.S. naval leadership in response. The terms of reference (TOR) directed that the study be based on Intergovernmental Panel on Climate Change (IPCC) scenarios and other peer-reviewed assessment. Therefore, the committee did not address the science of climate change or challenge the scenarios on which the committee's findings and recommendations are based. National Security Implications of Climate Change for U.S. Naval Forces addresses both the near- and long-term implications for U.S. naval forces in each of the four areas of the TOR, and provides corresponding findings and recommendations. This report and its conclusions are organized around six discussion areas—all presented within the context of a changing climate.
Keywords: Conflict and Security Issues; Transportation and Infrastructure

Polar Icebreakers in a Changing World: An Assessment of U.S. Needs - Transportation Research Board; National Research Council (The National Academies Press, 2007)
The United States has enduring national and strategic interests in the polar regions, including citizens living above the Arctic circle and three year-round scientific stations in the Antarctic. Polar icebreaking ships are needed to access both regions. Over the past several decades, the U.S. government has supported a fleet of four icebreakers—three multi-mission U.S. Coast Guard ships (the POLAR SEA, POLAR STAR, and HEALY) and the National Science Foundation's PALMER, which is dedicated solely to scientific research. Today, the POLAR STAR and the POLAR SEA are at the end of their service lives, and a lack of funds and no plans for an extension of the program has put U.S. icebreaking capability at risk. This report concludes that the United States should continue to support its interests in the Arctic and Antarctic for multiple missions, including maintaining leadership in polar science. The report recommends that the United States immediately program, budget, design, and construct two new polar icebreakers to be operated by the U.S. Coast Guard. The POLAR SEA should remain mission capable and the POLAR STAR should remain available for reactivation until the new polar icebreakers enter service. The U.S. Coast Guard should be provided sufficient operations and maintenance budget to support an increased, regular, and influential presence in the Arctic, with support from other agencies. The report also calls for a Presidential Decision Directive to clearly align agency responsibilities and budgetary authorities.
Keywords: Transportation and Infrastructure; Earth Sciences

Lessons and Legacies of International Polar Year 2007-2008 - National Research Council (The National Academies Press, 2012)
International Polar Year 2007-2008 (IPY) was an intense, coordinated field campaign of observations, research, and analysis. It was the largest, most comprehensive campaign ever mounted to explore Earth's polar domains. Legacies and Lessons of the International Polar Year 2007-2008 summarizes how IPY engaged the public to communicate the relevance of polar research to the entire planet, strengthened connections with the Indigenous people of the Arctic, and established new observational networks. Legacies and Lessons of the International Polar Year 2007-2008 also addresses the objectives articulated for IPY in the 2004 National Research Council report, A Vision for International Polar Year (NRC, 2004). These objectives include: suggestions for scientific communities and agencies to use the IPY to initiate a sustained effort aimed at assessing large-scale environmental change and variability in the polar regions, the need to explore new scientific frontiers from the molecular to the planetary scale, investment in critical infrastructure and technology to guarantee that IPY 2007-2008 leaves enduring benefits for the nation and for the residents of northern regions, as well as increase public understanding of the importance of polar regions in the global system. Legacies and Lessons of the International Polar Year 2007-2008 explains how activities at both poles led to scientific discoveries that provided a step change in scientific understanding and helped translate scientific knowledge into policy-relevant information. At a time when the polar regions are undergoing a transformation from an icy wilderness to a new zone for human affairs, these insights could not be more timely or more relevant. From outreach activities that engaged the general public to projects that brought researchers from multiple disciplines and several nations together, the legacies of IPY extend far beyond the scientific results achieved, and valuable lessons learned from the process will guide future endeavors of similar magnitude.
Keywords: Earth Sciences